Coeliac disease and obstetric and gynaecological disorders: where are we now?. Issue 4 (April 2019) - Schiepatti, Annalisa; Sprio, Elisa; Sanders, David S.; Lovati, Elisabetta; Biagi, Federico
Abstract : Coeliac disease (CD) is a chronic gluten-dependent enteropathy very common in the general population and characterized by an extremely heterogeneous clinical picture. Although its prevalence is growing worldwide, case-finding strategy remains the mainstay to diagnosis. Thus, correct identification of high-risk categories of patients who need to be tested for CD is an essential part of medical knowledge to a large number of specialists and primary care providers. In this regard, although CD might have a serious effect on women's reproductive health, a widespread consensus is lacking on which categories of obstetric and gynaecological disorders should be tested for CD. The aim of this review is to critically summarize the current literature relevant to CD and obstetric and gynaecological disorders and to provide practical proposals that may be helpful to clinicians involved in the management of these patients.